Cultural Competence Perspectives From Nurses in Four Asian Countries: A Qualitative Descriptive Study - Songwathana, Praneed; Chunuan, Sopen; Purinthrapibal, Shutiwan; Balthip, Karnsunaphat; Hui, Tao; Ibrahim, Kusman; Thi Thuy, Luu (Journal of Health Science and Medical Research, 2020)
Objective: This study aimed to describe the perception of cultural competence (CC) among nurses of four Asian countries. Material and Methods: A descriptive qualitative study was carried out, including fourteen nurses for in-depth interviews and 63 nurses for 8 focus group discussions being purposively selected from four Asian countries. Data were analyzed based on content analysis. Results: The participants defined CC as similar to cultural care, and described their CC in four main themes: (1) caring focus for patients with different cultures, (2) valuing holistic care/ patient-centered nursing, (3) preparing for living with God or Buddha, and (4) considering the social norms and patient rights. Assessment of the patient’s cultural background and myths contrary to medicine, along with having professional nursing knowledge, skills, and experience were the components of CC. Conclusion: The participants have addressed their CC in providing culturally, congruent care with a universal, holistic, and empathetic approach. Nurses should be trained to develop skills in multicultural care and language and made aware of their patients’ cultural beliefs. Further, CC scales for nurses working in the selected, four Asian countries should be developed.